Recreational forest landscape maintenance: an observation on selected recreational forest sites in Hungary - Hussein, Mohd. Kher (2014)
Recreational forest has being developed for the purposes of preserving and conserving natural forest from diminish. In order to make sure recreational forest sustainability and their existence is long-lasting, maintenance works need to carry out by the management. Furthermore, due to recreational forest landscapes is always the combine of natural landscape and human made elements, a proper and good maintenance plan need being established. Therefore, this study aims to understand how recreational forests being keep up towards sustainability in Hungary. Objective of the study is to explore and understand landscape maintenance practices in keeping pace with user needs and demands in Hungarian recreational forests. As a result, this study highlighted that landscape maintenance should include all landscape elements which are natural landscape and human made landscape elements in the maintenance program including park cleanliness. Maintenance works could be divides into three categories: daily, corrective and prevention. Their works need being planned according to daily, weekly, monthly and annually based on needs and requirements of landscape types. Proper and systematic landscape maintenance helps in increasing user satisfaction on recreational forest landscape development towards sustainability and long-lasting the park existence.